Determinantion of Formaldehyde in Tofu from Betung Banyuasin Market, South Sumatra - yeni Indriyani (Science Midwifery, 2021)
Formalin is a hazardous chemical substance to public health which is often used in tofu products. Tofu is a vegetable product usage as a source of protein derived from soybeans, a protein that is needed by humans growth. This study aims to test the presence or absence of formalin content in tofu sold in the Betung Banyuasin market, South Sumatra. A qualitative method is used in the form of a color test by adding turmeric solution. The results of the qualitative test showed that the tofu contained negative formalin. The color test was carried out using a turmeric solution. In conclude, of the color test showed that 6 negative samples contained formalin, indicated by the solution not changing, namely the orange color of the natural color of turmeric did not change